Simple chemical co-precipitation/calcination route for the synthesis of simulated synroc-B and synroc-C powders - Potdar, H. S.; Vijayanand, S.; Mohaideen, Kamal Khaja; Patil, K. R.; Joy, Pattayil Alias; Madhavan, R. Raja; Kutty, K. V. G.; Ambashta, Ritu D.; Wattal, P. K. (Materials Chemistry and Physics, 2010)
A simple chemical co-precipitation/calcination route was developed for the synthesis of simulated synroc-B and synroc-C powders using mostly nitrate salts as starting chemicals and 20% ammonia solution as precipitant. In this route, a mixed solution containing Al-nitrate, Ca-nitrate, Ba-nitrate, zirconyl nitrate and titanyl nitrate in the molar proportion required for synroc-B is added to dilute ammonia solution to precipitate these cations in the form of their hydroxides at room temperature by maintaining pH approximate to 10.5 during precipitation. Formation of a major fluorite phase with minor amounts of anatase, rutile and hollandite phases is observed in the powder obtained after calcination in air at 750 degrees C. Multiphase crystalline synroc-B matrix containing hollandite, perovskite, zirconolite, and rutile phases is obtained after sintering the heat treated powder in the form of pellets at 1230 degrees C for 4h in air. Similarly, pure synroc-C phases with 14 and 20% simulated waste loadings were synthesized following the same synthesis protocol. These pre-treated powders with a high surface area of similar to 25 m(2) g(-1) gave sintered ceramics having density of similar to 90% for 14 and 20% waste loadings. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Oxides; Sintering

Studies on the effect of sintering conditions on the magnetostriction characteristics of cobalt ferrite derived from nanocrystalline powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of the European Ceramic Society, 2014)
The effect of sintering conditions on the magnetostriction characteristics of sintered cobalt ferrite derived from nanocrystalline powders is studied. It is observed that the magnetostriction coefficient as well as the slope of the magnetostriction as a function of field depends on the microstructure of the sintered product. There is a direct correlation between the magnetostriction characteristics and density as well as porosity of the sintered products. Intragranular pores are found to be strongly influencing the magnetostriction characteristics. Similarly, correlation is found between the magnetostriction parameters and the Curie temperature, indicating the role of cation distribution which affects the magnetic anisotropy. Sintering the compacts made from nanocrystalline powders at 1450 degrees C for a very short duration is found to give high values of magnetostriction coefficient. However, higher values of magnetostriction at low magnetic fields are obtained for samples sintered at lower temperatures for longer duration and having relatively lower density. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cobalt ferrite; Magnetostriction; Microstructure; Nanocrystalline; Sintering